2020
DOI: 10.1029/2020pa004018
|View full text |Cite
|
Sign up to set email alerts
|

Delays, Discrepancies, and Distortions: Size‐Dependent Sediment Mixing and the Deep‐Sea Record of the Paleocene‐Eocene Thermal Maximum From ODP Site 690 (Weddell Sea)

Abstract: The deep-sea sedimentary record of Ocean Drilling Program Site 690 (Weddell Sea) has figured prominently in the study of an ancient (~56 Ma) global warming event referred to as the Paleocene-Eocene Thermal Maximum (PETM). Yet discrepancies in the timing, amplitude, and structure of the isotopic excursions marking the PETM exist between the bulk-carbonate and planktic foraminifer stable isotope (δ 13 C and δ 18 O) records of this reference section. A recent study invoked size-dependent sediment mixing (SDSM) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…4). Similarly weak isotopic enrichments are recorded in pre-PETM A. subsphaerica at Site 690 (Hupp et al 2019;Hupp and Kelly 2020) and in pre-PETM acarininids from ODP Site 689 (Si and Aubry 2018). Across all Southern Ocean studies, Acarinina shows no significant size-δ 13 C relationship in the middle of the core-PETM, during which Acarinina δ 13 C values collapse onto those of co-occurring Subbotina.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…4). Similarly weak isotopic enrichments are recorded in pre-PETM A. subsphaerica at Site 690 (Hupp et al 2019;Hupp and Kelly 2020) and in pre-PETM acarininids from ODP Site 689 (Si and Aubry 2018). Across all Southern Ocean studies, Acarinina shows no significant size-δ 13 C relationship in the middle of the core-PETM, during which Acarinina δ 13 C values collapse onto those of co-occurring Subbotina.…”
Section: Discussionmentioning
confidence: 65%
“…It is common for the largest individuals of photosymbiont-bearing species to show weaker size-δ 13 C fractionation effects than smaller individuals, which is attributed to ontogenetic effects such as gametogenic calcification, which could account for differences among size fractions. Hupp et al (2019) and Hupp and Kelly (2020) proposed a similar pattern during the onset of the PETM at Site 690 to be a preservational artifact of differential mixing depths and abundance changes across size fractions, an explanation that works equally well to explain the disconnect in isotopic changes across size fractions at Site 401, but not the differential response of acarininids and morozovellids to the PETM.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hupp and coworkers recently reported that cm‐scale discrepancies between bulk carbonate‐ and planktic foraminiferal δ 13 C values can arise from size‐dependent sediment mixing (SDSM), which may affect the stratigraphic position of a CIE onset for different size fractions (Hupp & Kelly, 2020; Hupp et al., 2019). The record presented here extends from 58 Ma to 50 Ma, spanning ∼25 meters with a mean sampling resolution of ∼0.5 m; thus, the trends reported here are much more protracted that those expected to arise from SDSM.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the excellent chemostratigraphic correlation shown amongst bulk sediment δ 13 C across widely separated sediment sections, the timing of onset of major climatic events sometimes appear to be offset between bulk sediment‐ and planktic foraminiferal δ 13 C records (Kirtland‐Turner et al., 2017). Such discrepancies could result from post‐depositional size‐dependent sediment mixing―broadly a taphonomic effect―which results in delays in the onset of isotope excursions recorded by finer foraminifers compared to the ones with larger tests (Hupp & Kelly, 2020; Hupp et al., 2019). These post‐depositional effects may affect interpretation of high‐resolution isotope records.…”
Section: Introductionmentioning
confidence: 99%